Myopic strabismus fixus convergens - Prakash Prem (Indian Journal of Ophthalmology, 1989)
A case report of myopic myositis, a rare entity, leading to strabismus fixus convergens, occurring in a high myope at the age of 46 years is presented. The possible differential diagnosis along with the aetiopathogenesis is discussed.